Sosialisasi Jamban Sehat di Dusun Petai Gayo, Desa Pagar Jati, Bengkulu Tengah dalam Perspektif Kelompok 50 KKN UIN Fatmawati Sukarno Bengkulu - Rahmatullah, Arif; Octafeani, Elsy; Budiman, Muhammad; Sufriadi, Rahmat (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This study aims to identify issues and raise community awareness about the importance of having proper sanitary facilities in Dusun Petai Gayo, Desa Pagar Jati, Bengkulu Tengah. The research employs a descriptive qualitative method to depict the phenomenon of sanitary facilities within the community. The findings indicate that many households lack adequate sanitary facilities due to a lack of awareness and economic factors. A sanitation awareness program was conducted to enhance understanding and provide information on the importance of maintaining cleanliness through proper sanitary facilities. The study also highlights that sanitary facilities meeting criteria such as preventing water contamination and maintaining environmental cleanliness are crucial for public health.